Education level, contraceptive communication, and IUD use among rural-to-urban migrants in China: A qualitative study. - Danielle Kane; Bing Han; Yu Chung (PLoS ONE)
Chinese rural-to-urban migrant workers have high rates of unintended pregnancy, yet many are reluctant to choose the most effective forms of contraception, such as IUDs (intrauterine devices). Those who do are often socioeconomically disadvantaged, a finding that contradicts much health research, namely that higher SES individuals can access better healthcare. This puzzle highlights the need to understand better migrant workers' contraceptive decision-making. This paper reports findings from interviews with 91 migrant workers. Across educational backgrounds, IUD use usually followed contraceptive-related communication. Female interviewees with less education were more likely to have contraception-related discussions, including with doctors, in which the benefits of IUDs emerged. Typically, however, these conversations happened after a pregnancy. The findings suggest a need for public awareness campaigns that destigmatize discussion of contraception and interventions targeted by education level.